(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Our study in this paper focused on the criminal confrontation of terrorist organizations In Syrian legislation, which was stipulated in the Anti-Terrorism Law No. 19 of 2012, and the main idea of ​​the research revolves around our question about the effectiveness of the modern criminal policy of the Syrian legislator in facing crimes related to terrorist organizations, and accordingly we talked about the foundations of criminalizing organizations Terrorism, which constitute the basic controls that the legislator has decided to criminalize terrorist organizations with regard to their concept, composition, and purpose, as we have also discussed the images of crimes of terrorist organizations, which represent the practical implications of the main controls T stipulated by the legislator, and therefore it was necessary to talk about the detailed types of such crimes through the statement of its corners and penalties and aggravating circumstances of the punishment.